A cDNA microarray for Crassostrea virginica and C. gigas. - Jenny, Matthew J; Chapman, Robert W; Mancia, Annalaura; Chen, Yian A; Mckillen, David, J.; Trent, Hal; Lang, Paul; Escoubas, Jean-Michel; Bachere, Evelyne; Boulo, Viviane; Liu, Z John; Gross, Paul S; et al. (Marine Biotechnology, 2007)
International audience The eastern oyster, Crassostrea virginica, and the Pacific oyster, C. gigas, are species of global economic significance as well as important components of estuarine ecosystems and models for genetic and environmental studies. To enhance the molecular tools available for oyster research, an international group of collaborators has constructed a 27,496-feature cDNA microarray containing 4460 sequences derived from C. virginica, 2320 from C. gigas, and 16 non-oyster DNAs serving as positive and negative controls. The performance of the array was assessed by gene expression profiling using gill and digestive gland RNA derived from both C. gigas and C. virginica, and digestive gland RNA from C. ariakensis. The utility of the microarray for detection of homologous genes by cross-hybridization between species was also assessed and the correlation between hybridization intensity and sequence homology for selected genes determined. The oyster cDNA microarray is publicly available to the research community on a cost-recovery basis.